Active methodologies and learning of scientific competence: consistency over time - Hidalgo Navarrete, José; De la Blanca De la Paz, Soledad; Burgos Bolós, Consuelo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The use of active methodologies for science education in pre primary and primary education promotes knowledge structures that are consolidated over time. Our hypothesis is that students who have been trained on the scientific method in the initial stages will go on applying this knowledge in their everyday life. To this end, we have worked with simple machines because they are present in a multitude of everyday situations. A t-test was used between the different groups and the results reveal the situations in which the differences are significant after 6 years. It is the responsibility of educational institutions to use methodologies that lead to the development of competences, including scientific competence.